Models of Building Organizational Structure of Developing Highly-Technological Enterprises - V. D. Kolychev; N. A. Budanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article discusses issues dealing with building organizational structure of developing enterprises by using both quantitative and qualitative criteria. In the research the authors used the best practices of highly-technological companies. To solve the problem of organizational structure upgrading methods of assessing key indicators of organization and its division work efficiency were used. The authors propose a number of criteria and methods aimed at structure upgrading, which could be exploited in applied activity of industrial science-intensive enterprises and organizations. On the basis of mathematical methods of modeling and optimization the authors formulated suggestions concerning rational building of organizational structure and calculating parameters of completeness of structural divisions by administrative and managerial personnel.